Rules and procedures regarding the functioning of modern operating theatre - Morawik, Iwona; Jabłoński, Mirosław (Polish Journal of Public Health, 2011)
Over a span of years, following the development of operating techniques, the rules and procedures regarding the functioning of operating theatre have been changing. The operating room, however, still constitutes its most important element. It is here where state-of-the-art technologies are realized and a patient’s fate and future often is decided. It is of utmost importance to assure that the surgery is performed with the use of the best quality medical equipment under the highest hygienic and sanitary standards.Supplying operating rooms with modern medical equipment and integrated control system will make it possible to perform a bigger number of operations in a more efficient and safer way. Moreover, an effective operating room should be spacious, well-illuminated, equipped with an air-conditioning system with a laminar-flow ventilation.Raising staff awareness, training of personnel as well as a proper level of scrub nurse education contributes considerably to lowering the risk of infections which are the most common and the most serious postoperative complications.A properly managed, modern operational suite should be functional, reliable, and, at the same time, cost-effective. It should also be a rewarding investment which pays for itself. An operational suite which meets EU regulations and norms often creates the image of the whole hospital